Haanz street food / Hafizuddin Zakare ... [et al.] - Zakare, Hafizuddin; Mohd Nazri, Muhammad Zulfadly; Amaluddin, Nasrin Nur Qasdina; Zawawi, Muhamad Arif Adham; A.Rahman, Aliya (2015)
This business is based on partnership where it consists of five (5) members which hold important positions in the company such as General Manager, Administration Manager, Marketing Manager, Operational Manager and Financial Manager. The business capital is amounted to RM25,000 where the total contribution of each member is RM5,000 and the rest RM20,000 is from bank loan. HAANZ Street Food is a company which focuses on food production in Malaysia. Our company sell food from a food truck that are most popular in Kuala Lumpur and also overseas. Our company sells mainly Mexican food that is burrito, our signature dishes that can make your taste bud turns excited. The yummy and delicious taste of the fillings of the burrito plus with a tender and soft tortilla bread as the wrapping of the burrito can make people tum crazy over the foods. Moreover, the simple steps and ingredients give a lot of benefits to our company and we are highly confident that our market can be easily developed and spread in Malaysia. To make it more attractive and interesting, we decided to make some innovation by implying our creativity and modem element in this foods and drinks making. Nowadays, flavor is one of the important things in any products making so a new different flavor might be a new attraction to people. We have done some research that Johor Bahru is one of the city that have life during night. So with our new innovation, they can just grab a food or snack and eat while walking. It is easy and simple as that. With loan given as a support from bank we are hoping and wishing to make HAANZ Street Food able to achieve outstanding demand from consumer. Our business is expected to commence on 2017 and our vision is to make our company a well-known, established and satisfied by our customer in order to expand our HAANZ Street Food to attract other food company to deal with us with a better price. This will be realized by the full cooperation and efforts among the partners to promote company. Based on the objectives above, we are venturing into food industry. HAANZ Street Food production has the potential of being a profitable business if it is done in modem way With large scale and systematically managed. We will expect that our business will become more developed in the near future because with the new innovation in our HAANZ Street Food, the demand will increase not only during any occasion but it might be a new daily snack. This will give more advantages for Us to make our product more profitable and stable in the long run.